(untitled) (Heritage, 2024)
The paper focuses on the analysis of the practical application of the Law on the Prevention of Domestic Violence which prescribes a proactive way of work of competent authorities. Research results have been presented, encompassing registered events with elements of domestic violence in the Republic of Serbia in the 2018 – 2023 period, as well as the measures taken by the competent authorities (police, public prosecutor’s office, and court) in order to prevent domestic violence and protect victims. A comprehensive analysis of the practical implementation of the law was made, where the data related to statistical regions in the Republic of Serbia were compared in order to establish the effects of the law implementation in each part of the country. The research results showed that the work of competent authorities needs to be standardized in the future as there were significant differences in the manner of operation. The problems encountered in the practical implementation of certain legal provisions were considered and certain recommendations were given. The work of coordination and cooperation groups formed in 63 areas throughout Serbia, whose primary task is to take timely and effective measures aimed at protecting victims, defined by the individual victim protection plan, following a high-quality comprehensive risk assessment regarding the possibility of recurrence of violence and the occurrence of the gravest consequences for the victim. The author concludes that the implementation of the pre-crime concept in this area and targeting potential perpetrators prior to commission of the criminal offence, regardless of whether the offence would ever be committed, renders certain positive effects which are mostly reflected in the decrease in the number of the most serious forms of domestic violence which result in the loss of a family member’s life, especially those affecting female victims of violence, who are the most threatened by this type of crime. Achieving this goal was one of the reasons for passing the law under review.